Translation: A Key Component of a Hundred-Year Project - Samphel, Tsondue; Namgyal, Dadul; Drongbu, Dawa Tsering; Khangsar, Karma Tenzin (Frontiers in Communication, 2021)
The Emory-Tibet Science Initiative (ETSI) has embarked on a historic endeavor of introducing a systematic and sustainable science education program within the traditional Tibetan monastic institutions. His Holiness the Dalai Lama, who conceived and supports this initiative, calls it a hundred-year project. From the very beginning, translation from English to Tibetan has been an integral part of this project because of the need to prepare course materials as well as to facilitate on-site classes and lab activities in the Tibetan language. Our translation process involves not just conveying novel and foreign concepts across cultures but doing so with a scientific language peppered with technical terms that are not readily representable in the target language. In addition to the linguistic barriers, cultural and technical ones further complicate the process of communication. A case in point is the concept of life, or correlation versus causation, or the view that consciousness is an emergent property of the brain, where each construct has its corresponding but differing concept in Tibetan Buddhism. When engaging with such existing parallel yet divergent terms or concepts, the translators must strike a delicate balance and avoid forsaking the distinctive characteristics and connotations involved. In this article, the ETSI translation team shares its journey—highlighting the needs felt, challenges faced, and solutions sought. We discuss the translation principles guiding our work and the handling of such scientific features as graphs, acronyms, units, chemical names, and formulas. We hope our work will inspire other similar projects around the globe and encourage them to continue bridging barriers to cross-cultural dialogues, promoting cross-fertilization of knowledge for human flourishing.